A retrospective study of acquired canine thrombocytopaenia - Abd Rahman, Nor Yasmin; Hamzah, Hazilawati; Abdullah, Rasedee; Rahman, Nor Alimah (2010)
Acquired canine thrombocytopaenia is a common canine haemostatic disorder in veterinary medicine. The purposes of this study were to investigate patterns of thrombocytopaenia in 2007 and 2008 on monthly and yearly basis, respectively, in the University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM), to study the aetiology of acquired thrombocytopaenia, to describe signalment, management, and disease preventive measure of the thrombocytopaenic dog, and lastly to relate significant findings of the haematological and biochemical parameters to the thrombocytopaenia. The data were obtained from Haematology and Clinical Biochemistry Laboratory, Faculty of Veterinary Medicine, UPM and the patient medical records were obtained from UVH. All data were reported based on a descriptive analysis. Results showed the numbers of dogs with acquired thrombocytopenia were 67 and 69 in 2007 and 2008, respectively. Most of the cases were reported in January 2007, and May and December 2008. Acquired canine thrombocytopenia occurred in any sex or breed. The most significant haematological and biochemical findings of the thrombocytopaenic dogs were regenerative left shift, regenerative anaemia, and hyperglobulinaemia. The aetiology of acquired thrombocytopaenia in dog was mostly from infection-and inflammation-associated diseases. In conclusion, thrombocytopaenia is a prevalent and potentially important diagnostic finding in a variety of disease states.